Comparative Hydrological and Geoelectrical Study on the Quaternary Aquifer in the Deltas of Wadi Badaa and Ghweiba, El Ain El Sukhna Area, Northwest Suez Gulf, Egypt - M. M. El Osta; A. El. El Sheikh; M. S. Barseem (International Journal of Geophysics)
El Ain El Sukhna area was selected in the last ten years to initiate many governmental and investmental programs. The different activities in that area depend mainly on the groundwater of the Quaternary aquifer, which forms the main water bearing strata. In the present work, twenty one geoelctrical soundings using the Schlumberger configuration are carried out at selected sites especially in missing parts from wells to delineate the groundwater setting in such sites. Eight of them are conducted in the close vicinity of water wells, where lithologs and pumping test data of these wells are available to relate hydrologic and geoelctric measurements. The pumping tests data are analyzed by using AQTESOLV program and the geolectrical sounding data were interpreted by partial curve matching technique to obtain the initial parameters. The results indicated that, the transmissivity is found to be closely related with transverse resistance and the hydraulic conductivity with average transverse resistivity, while the salinity is inversely related with resistivity. Finally, priority map for drilling water wells is constructed to make the results more illustrative and useful for decision maker. The promising area for drilling is located at the western portion of the study region.